Lightweight flame-retardant impact-resistant protective material and preparation method thereof
By introducing phosphorus-containing organosilane-containing functionalized hollow glass microspheres into impact-resistant shear hardening gels, combining alkali solution and boric acid materials, the problem that existing protective materials cannot take into account lightweight flexibility and flame retardant and heat insulation. The preparation of lightweight flame retardant and impact-resistant protective materials is realized, with efficient energy dissipation and impact-resistant properties, and simplified the synthesis process.
Patent Information
- Application Number
- CN202411581593.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
While providing impact resistance, existing protective materials cannot take into account lightweight flexibility and flame retardant and thermal insulation properties, and the synthesis process is complex, energy consumption is high, and reagents are expensive.
Introduce phosphorus-containing organosilane-functionalized hollow glass microspheres into impact-resistant shear hardening gels, and use alkali solution treatment and silane coupling agent modification, combining phosphorus-containing flame retardant and boric acid materials to prepare lightweight flame retardant Impact protection material. The method includes pretreatment of hollow glass microspheres, silane coupling, phosphorus-containing functionalization and molding processes, simplifying the synthesis steps and reducing energy losses.
The obtained materials have light weight, impact resistance, flame retardant and heat insulation properties, which are easy to synthesis and energy-saving. They are suitable for microspheres of different particle sizes, enhancing the energy absorption and impact properties of the materials.
Smart Images

Figure CN119264668A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and specifically relates to a lightweight flame-retardant and impact-resistant protective material and a preparation method thereof. Background Art
[0002] Ubiquitous mechanical impacts pose potential risks to safety protection in transportation and sports applications, while thermal mechanical impacts such as house collapse and wood falling caused by high-temperature fires also pose a great threat to personal safety. Therefore, it is particularly urgent to develop advanced high-performance impact-resistant flame-retardant protective materials to ensure personal safety.
[0003] At present, most of the commonly used protective materials are based on alloys and ceramics. For example, protective materials based on alloys or ceramics, such as bulletproof vests, can be used to protect soldiers and police. However, this hard armor can neither protect the movable body organs (joints, neck, etc.) well nor provide good lightness and comfort for the wearer. Therefore, it is of great significance for protective materials to combine strong impact resistance with comfortable lightness and flexibility.
[0004] It is also based on this that the technical solution of the present invention is proposed. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention designs a lightweight flame retardant impact-resistant protective material and a preparation method thereof. A lightweight flame retardant impact-resistant shear reinforced gel protective material is obtained by introducing phosphorus-containing organosilane functionalized hollow glass microspheres (HGM) into the impact-resistant shear hardening gel. The protective material is lightweight, has high energy dissipation and impact resistance, and also has flame retardant and heat-insulating properties. At the same time, a synthesis method is provided which is simple and easy to operate, has a short synthesis time, low energy loss, and uses cheap and readily available reagents.
[0006] The solution of the present invention is to provide a method for preparing a lightweight flame retardant and impact resistant protective material, the preparation method comprising the following steps: (1) mixing and stirring the hollow glass microspheres with an alkaline solution, and then filtering and drying to obtain pretreated hollow glass microspheres; (2) adding the hollow glass microspheres to an ethanol aqueous solution, adding a silane coupling agent γ-aminopropyltriethoxysilane (KH550) under heating conditions, continuously stirring, centrifuging, washing, and drying in sequence to obtain hollow glass microspheres modified by a silane coupling agent; (3) mixing the hollow glass microspheres modified by the silane coupling agent with a solvent, adding a solution of a phosphorus-containing flame retardant, reacting under heating conditions, centrifuging, washing, and drying in sequence to obtain phosphorus-containing organosilane functionalized hollow glass microspheres; (4) The organosilicon material and the boric acid material are stirred and mixed, and then the phosphorus-containing organosilane functionalized hollow glass microspheres and methanol are added, and the temperature is raised to react under stirring conditions to obtain a mixture; the mixture is then poured into a mold and placed in a mold for molding, thereby obtaining a lightweight flame retardant and impact resistant protective material.
[0007] Preferably, in step (1), the particle size of the hollow glass microspheres is 20-100 μm; and / or, the concentration of the alkaline solution is 1-10 wt %; And / or, the alkaline solution is one or a combination of two or more of a sodium hydroxide solution, an ammonia solution, and a sodium carbonate solution.
[0008] Preferably, in step (2), the concentration of ethanol in the ethanol aqueous solution is 10-40 vol%.
[0009] Preferably, in step (3), the phosphorus-containing flame retardant is one or a combination of two or more of ammonium polyphosphate (APP), hexachlorocyclotriphosphazene (HCCP), and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO).
[0010] Preferably, in step (4), the organosilicon material is hydroxyl-terminated polydimethylsiloxane (PDMS), and the viscosity of the organosilicon material is 20-25000 cst.
[0011] Preferably, in step (4), the boric acid material is one or a combination of two or more of tetrahydroxydiboron (B2H4O4), phenylboric acid (PhB(OH)2), and boric acid (H3BO3).
[0012] Preferably, in step (1), the mixing temperature is 80-85°C, the mixing time is 2-3 h; the drying time is 20-24 h; And / or, in step (2), the heating condition is heating to 70-75° C., and the continuous stirring time is 2-3 h; And / or, in step (3), the heating condition is 60-80°C, and the reaction time is 2-8 h; And / or, in step (4), the temperature of the temperature-raising reaction is 85-95°C.
[0013] Based on the same technical concept, the present invention further provides a lightweight flame retardant and impact resistant protective material obtained by the above preparation method.
[0014] The beneficial effects of the present invention are: 1. In the modified hollow glass microspheres studied in the present invention, the active sites of Si-OH bonds are increased by alkali leaching of the hollow glass microspheres, and the surface structure of the hollow microspheres is optimized, so that the hollow glass microspheres have better mechanical properties and stability.
[0015] 2. The material prepared by this method is flame retardant and heat-insulating. When the microspheres are broken under dynamic impact, it is beneficial to absorb more kinetic energy, and the influence on its flame retardant performance is different. The stronger the interface interaction with the matrix, the higher the flame retardant performance and the better the impact effect.
[0016] 3. This method is applicable to hollow glass microspheres with different particle sizes, and can obtain modified hollow glass microspheres with different energy absorption properties; the shear thickening behavior and relaxation time scale of the outer layer shear hardening gel with different structures have different effects on the impact performance of the protective material, but its impact resistance essence still lies in the unique BO dynamic bond, which makes its modulus increase significantly with the increase of external strain rate; the preparation method of the composite material of this method is simple and easy to operate, the synthesis time is short, the energy loss is small, and the reagents used are cheap and easy to obtain. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 For infrared spectrum.
[0019] Figure 2 is the XRD pattern.
[0020] Figure 3 is a scanning electron microscope and elemental distribution map; among them: Figure 3 a in the figure is a scanning electron microscope image of HGM after NaOH etching (Mag=500X, i.e., magnification 500 times); Figure 3 b is a scanning electron microscope image of HGM-APP after functional modification with a phosphorus-containing flame retardant (Mag = 500X, i.e., magnification 500 times); Figure 3 c in the figure is a scanning electron microscope image (Mag=1500X, i.e., magnification 1500 times) of HGM-APP after functional modification with a phosphorus-containing flame retardant; Figure 3 The d in the figure is the distribution diagram of the elements on the surface of HGM-APP.
[0021] Figure 4 This is the modulus-frequency scanning curve. DETAILED DESCRIPTION
[0022] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0023] Example 1
[0024] The present invention provides a method for preparing a lightweight flame retardant and impact resistant protective material, the preparation method comprising the following steps: (1) 5 g of hollow glass microspheres (HGM) were added to 150 mL of NaOH solution (2 wt%), stirred at 85 °C for 2 h, filtered, and dried at room temperature for 24 h to obtain pretreated hollow glass microspheres; (2) adding 2 g of the pretreated hollow glass microspheres to 40 mL of ethanol aqueous solution (30 vol%), adding 2 mL of KH550 at 75°C, stirring for 2 h, centrifuging, washing, and drying in sequence to obtain hollow glass microspheres modified by a silane coupling agent (HGM-KH550); (3) The HGM-KH550 was mixed and dispersed with water to obtain a HGM-KH550 dispersion (2 g / 40 mL); an ammonium polyphosphate (APP) aqueous solution (0.2 g / mL) was slowly dripped into the HGM-KH550 dispersion, and after reacting at 60° C. for 2 h, HGM-APP was obtained by centrifugation, washing, and drying; (4) Add high viscosity (17000-25000 cSt) hydroxyl-terminated PDMS and low viscosity (20-80 cSt) hydroxyl-terminated PDMS in a mass ratio of 1:1 into a reactor, then add B2H4O4, HGM-APP and 40 mL of methanol, heat to 90°C for reaction and evacuate to obtain a mixture; then pour the mixture into a mold for molding to obtain a lightweight flame retardant and impact resistant protective material. Among them, B2H4O4 accounts for 1 wt% of the total amount of PDMS, and HGM-APP accounts for 9 wt% of the total amount of PDMS.
[0025] Example 2
[0026] The present invention provides a method for preparing a lightweight flame retardant and impact resistant protective material, the preparation method comprising the following steps: (1) 5 g of hollow glass microspheres HGM were added to 150 mL of NaOH solution (2 wt%), stirred at 85 °C for 2 h, filtered, and dried at room temperature for 24 h to obtain pretreated hollow glass microspheres; (2) adding 2 g of the pretreated hollow glass microspheres to 40 mL of ethanol aqueous solution (30 vol%), adding 2 mL of KH550 at 75°C, stirring for 2 h, centrifuging, washing, and drying in sequence to obtain hollow glass microspheres modified by a silane coupling agent (HGM-KH550); (3) 2 g of the HGM-KH550 was mixed and dispersed with 150 mL of tetrahydrofuran (THF), and then 10 mL of triethylamine (TEA) was added and stirred for 1 h under a nitrogen atmosphere to obtain a HGM-KH550 dispersion; a THF solution (0.04 g / mL) of hexachlorocyclotriphosphazene (HCCP) was slowly dripped into the HGM-KH550 dispersion, and the mixture was reacted at 80° C. for 8 h, and then centrifuged, washed, and dried to obtain HGM-PZE; (4) Add high viscosity (17000-25000 cSt) hydroxyl-terminated PDMS and low viscosity (20-80 cSt) hydroxyl-terminated PDMS in a mass ratio of 1:1 into a reactor, then add B2H4O4, HGM-PZE and 40 mL of methanol, heat to 90°C for reaction and evacuate to obtain a mixture; then pour the mixture into a mold for molding to obtain a lightweight flame retardant and impact resistant protective material. Among them, B2H4O4 accounts for 1 wt% of the total amount of PDMS, and HGM-PZE accounts for 9 wt% of the total amount of PDMS.
[0027] Example 3
[0028] The present invention provides a method for preparing a lightweight flame retardant and impact resistant protective material, the preparation method comprising the following steps: (1) 5 g of hollow glass microspheres HGM were added to 150 mL of NaOH solution (2 wt%), stirred at 85 °C for 2 h, filtered, and dried at room temperature for 24 h to obtain pretreated hollow glass microspheres; (2) adding 2 g of the pretreated hollow glass microspheres to 40 mL of ethanol aqueous solution (30 vol%), adding 2 mL of KH550 at 75°C, stirring for 2 h, centrifuging, washing, and drying in sequence to obtain hollow glass microspheres modified by a silane coupling agent (HGM-KH550); (3) The HGM-KH550 was mixed and dispersed with water to obtain a HGM-KH550 dispersion (2 g / 40 mL); an ammonium polyphosphate (APP) aqueous solution (0.2 g / mL) was slowly dripped into the HGM-KH550 dispersion, reacted at 60° C. for 2 h, and then centrifuged, washed, and dried at room temperature to obtain HGM-APP; (4) Add hydroxyl-terminated PDMS (2500-4000 cSt) to the reactor, heat it to 100°C, add H3BO3 in small amounts and multiple times according to the ratio of hydroxyl-terminated PDMS to boric acid (H3BO3) hydroxyl group of 1:1, add HGM-APP evenly under stirring, continue to heat to 150°C, keep warm for 45 minutes, pour the mixture into a mold and cool it to obtain a lightweight flame retardant and impact resistant protective material. Among them: HGM-APP accounts for 9 wt% of the total PDMS.
[0029] Example 4
[0030] The present invention provides a method for preparing a lightweight flame retardant and impact resistant protective material, the preparation method comprising the following steps: (1) 5 g of hollow glass microspheres HGM were added to 150 mL of NaOH solution (2 wt%), stirred at 85 °C for 2 h, filtered, and dried at room temperature for 24 h to obtain pretreated hollow glass microspheres; (2) adding 2 g of the pretreated hollow glass microspheres to 40 mL of ethanol aqueous solution (30 vol%), adding 2 mL of KH550 at 75 °C, stirring for 2 h, centrifuging, washing, and drying in sequence to obtain hollow glass microspheres modified by silane coupling agent (HGM-KH550); (3) 2 g of the HGM-KH550 was mixed and dispersed with 150 mL of tetrahydrofuran (THF), and then 10 mL of triethylamine (TEA) was added and stirred for 1 h under a nitrogen atmosphere to obtain a HGM-KH550 dispersion; a THF solution (0.04 g / mL) of hexachlorocyclotriphosphazene (HCCP) was slowly dripped into the HGM-KH550 dispersion, and the mixture was reacted at 80° C. for 8 h, and then centrifuged, washed, and dried to obtain HGM-PZE; (4) Add hydroxyl-terminated PDMS (2500-4000 cSt) to the reactor, heat it to 100°C, add H3BO3 in small amounts and multiple times according to the ratio of hydroxyl-terminated PDMS to boric acid (H3BO3) hydroxyl group of 1:1, add HGM-PZE evenly under stirring, continue to heat to 150°C, keep warm for 45 minutes, pour the mixture into a mold and cool it to obtain a lightweight flame retardant and impact resistant protective material. Among them: HGM-PZE accounts for 9 wt% of the total PDMS.
[0031] Comparative Example 1
[0032] High viscosity (17000-25000 cSt) hydroxyl-terminated PDMS and low viscosity (20-80 cSt) hydroxyl-terminated PDMS and B2H4O4 in a mass ratio of 1:1 are added to a reactor for stirring, with B2H4O4 accounting for 1% of the total PDMS. The temperature is raised to 90°C for reaction, vacuum is drawn, and the mixture is then poured into a mold for cooling to obtain a protective material.
[0033] Comparative Example 2
[0034] Add hydroxyl-terminated PDMS (2500-4000 cSt) into the reactor, heat it to 100°C, add H3BO3 in small amounts and multiple times according to the ratio of hydroxyl-terminated PDMS to boric acid (H3BO3) hydroxyl group of 1:1, continue stirring and heat to 150°C, keep warm for 45 minutes, pour the mixture into a mold and cool it to obtain a protective material.
[0035] Verification Example
[0036] The materials of Examples 1 to 4 and Comparative Examples 1 to 2 were tested with a thickness of 1 mm. The test results are shown in Table 1.
[0037] Table 1
[0038] In order to study the impact resistance of the protective material, a 4 g drop ball impact test was carried out at a height of 80 and 60 cm using a drop ball test device equipped with a force sensor. Among them, the blank sample is the drop ball directly contacting the force sensor in the impact test, and the other test samples are all placed on the force sensor as a buffer material. The 1mm thick sample sheet is placed on the force sensor for testing. From the test results in Table 1, it can be concluded that when there is no buffer material on the force sensor, that is, the blank sample, the detected force increases instantly when the steel ball hits the force sensor. In contrast, after the buffer material is placed, the maximum force transmitted is significantly reduced after the steel ball hits the surface. Among them, at a height of 60 cm, the maximum force transmitted by Example 1 (59.51 N) is about 74% of that of Example 2 (80.42 N), which indicates that the force attenuation rate of Example 1 is higher when it is used as a buffer material. At the same addition amount of phosphorus-modified hollow glass microspheres, at different heights, Examples 1 and 2 with a more stable diborane oxygen bond structure both show better impact resistance than Examples 3 and 4 with a single boron oxygen bond structure. Compared with the blank sample, the maximum force transmitted by Example 1 at 80 cm and 60 cm heights is attenuated by 96.4% and 93.6%, respectively. In addition to the interface interaction between the hollow glass microspheres modified by different phosphorus-containing flame retardants and the matrix, the shear hardening behavior exhibited by the supramolecular network of the diboron oxygen bond structure is closer to a solid state. This is based on the stronger electron deficiency of the boron atoms in the diboron structure, and the diboron oxygen coordination bonds have more coordination states and higher bond energy. The flame retardant test results of microcalorimetry found that the effect of reducing the maximum heat release rate of the matrix by ammonium polyphosphate modified hollow glass microspheres (Examples 1 and 3) is better than that of polyphosphazene modified hollow glass microspheres (Examples 2 and 4), which may be related to the interface interaction between the two and the matrix and the combustion carbonization mechanism.
[0039] Furthermore, Figure 1 is the infrared spectrum, Figure 1 It can be seen that HGM is at 799 and 1069 cm -1 The symmetric and antisymmetric stretching vibration peaks of Si-O-Si appeared at 463 cm -1 The bending vibration peak of Si-O-Si appears at 3471 cm -1 The stretching vibration peak of NH appears at 1035 cm -1 The stretching vibration peak of methoxy group appeared at 1092 cm -1 The newly added peak at is attributed to the POP bond.Infrared test shows that phosphorus-functionalized hollow glass microspheres have been successfully prepared.
[0040] Figure 2 is the XRD pattern. It can be seen from Figure 2 that: for the X-ray diffraction (XRD) patterns of HGM and HGM-APP, the broad peaks at 2θ = 15 - 35º belong to amorphous silica. The basic broad peak morphology of the HGM-APP curve after the hollow glass microspheres are functionalized and modified with phosphorus at 2θ = 15 - 35º has not changed significantly, while new diffraction peaks attributed to APP appear at 2θ = 11.58º, 23.2º, 30.52º and 35.34º.
[0041] Figure 3 are the scanning electron microscope and element distribution maps. It can be seen from Figure 3 that: the surface of HGM after being etched by NaOH is rough, with a small amount of tiny particles attached ( Figure 3 a in). After being functionalized and modified with a phosphorus-containing flame retardant, there are obvious protrusions on the surface of HGM-APP ( Figure 3 b in). At a magnification, it can be observed that the surface of a single HGM-APP is non-uniformly covered with layered substances of different thicknesses ( Figure 3 c in), which is the reason for the successful coating of APP. In addition, by using an energy dispersive spectrometer (EDS) to test the element distribution on the surface of HGM-APP, it is found that the coating layer on the surface of HGM-APP contains elements O, P, C and N ( Figure 3 d in). Among them, the P element comes from APP, the N element mainly comes from APP and KH550, and the C element comes from KH550. The element distribution shows that the phosphorus-containing flame retardant APP has been successfully grafted and modified on HGM.
[0042] Figure 4 is the modulus-frequency scanning curve graph, specifically the oscillatory frequency scanning of pure PDBS from 0.01 to 100 Hz at different temperatures (0, 20, 40, 60 and 80 °C). The results show that PDBS is a shear-enhanced material with a frequency-dependent viscoelastic modulus. The storage modulus (G′) increases linearly at low frequencies and then reaches a plateau, while the loss modulus (G′′) reaches a maximum near the transition point of G´. There is an intersection point of an angular frequency ω c where G′′ is equal to G'. When ω < ω c , PDBS is in a liquid state (G′ < G′′), and when ω > ω c , PDBS is in a solid state (G′ > G′′). The intersection frequency gradually increases with the increase of temperature, indicating that PDBS gradually changes from elastic to viscous properties with the increase of temperature.
[0043] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a lightweight flame retardant and impact resistant protective material, characterized in that: The preparation method comprises the following steps: (1) mixing and stirring the hollow glass microspheres with an alkaline solution, and then filtering and drying to obtain pretreated hollow glass microspheres; (2) adding the hollow glass microspheres to an ethanol aqueous solution, adding a silane coupling agent γ-aminopropyltriethoxysilane under heating conditions, continuously stirring, centrifuging, washing, and drying in sequence to obtain hollow glass microspheres modified with a silane coupling agent; (3) mixing the hollow glass microspheres modified by the silane coupling agent with a solvent, adding a solution of a phosphorus-containing flame retardant, reacting under heating conditions, centrifuging, washing, and drying in sequence to obtain phosphorus-containing organosilane functionalized hollow glass microspheres; (4) The organosilicon material and the boric acid material are stirred and mixed, and then the phosphorus-containing organosilane functionalized hollow glass microspheres and methanol are added, and the temperature is raised to react under stirring conditions to obtain a mixture; the mixture is then poured into a mold and placed in a mold for molding, thereby obtaining a lightweight flame retardant and impact resistant protective material.
2. The method for preparing a lightweight flame retardant and impact resistant protective material according to claim 1, characterized in that: In step (1), the particle size of the hollow glass microspheres is 20-100 μm; and / or, the concentration of the alkaline solution is 1-10 wt %; And / or, the alkaline solution is one or a combination of two or more of a sodium hydroxide solution, an ammonia solution, and a sodium carbonate solution.
3. The method for preparing a lightweight flame retardant and impact resistant protective material according to claim 1, characterized in that: In step (2), the concentration of ethanol in the ethanol aqueous solution is 10-40 vol%.
4. The method for preparing a lightweight flame retardant and impact resistant protective material according to claim 1, characterized in that: In step (3), the phosphorus-containing flame retardant is one or a combination of two or more of ammonium polyphosphate, hexachlorocyclotriphosphazene, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
5. The method for preparing a lightweight flame retardant and impact resistant protective material according to claim 1, characterized in that: In step (4), the organic silicon material is hydroxyl-terminated polydimethylsiloxane, and the viscosity of the organic silicon material is 20-25000 cst.
6. The method for preparing a lightweight flame retardant and impact resistant protective material according to claim 1, characterized in that: In step (4), the boric acid material is one or a combination of two or more of tetrahydroxydiboron, phenylboric acid, and boric acid.
7. The method for preparing a lightweight flame retardant and impact resistant protective material according to claim 1, characterized in that: In step (1), the mixing temperature is 80-85°C, the mixing time is 2-3 h; the drying time is 20-24 h; And / or, in step (2), the heating condition is heating to 70-75°C, and the continuous stirring time is 2-3 h; And / or, in step (3), the heating condition is 60-80°C, and the reaction time is 2-8 h; And / or, in step (4), the temperature of the temperature-raising reaction is 85-95°C.
8. The lightweight flame retardant and impact resistant protective material obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method of modifying hollow glass microbeads with ionic liquid and flame-retarding thermoplastic polyurethane elastomer with the modified hollow glass microbeads as flame retardant
CN106916336A
Cold flow inhibition type flame-retarding and impact hardening gel as well as preparation method and application thereof
CN109504090A
Cited By
Impact-resistant flame-retardant gel material and preparation method thereof
CN121159930A